Characteristics of Intertrochanteric Femur Fracture at Bali Mandara General Hospital - Prabawa, I Made Ngurah Angga; Sanjaya, Putu Agung Wirahadi (The Hip and Knee Journal, 2024)
Intertrochanteric femur fracture is an extracapsular fracture that occurs along the line that is located between the greater and lesser trochanters. This study aims to determine the characteristics of intertrochanteric femur fracture cases at Bali MandaraGeneral Hospital Denpasar from January to August 2022. The method in tThis study with retrospective descriptive study evaluated the characteristics of intertrochanteric femur fracture patients at Bali Mandara General Hospital Denpasar from January to August 2022. The patient’s characteristics included in this study were age, sex, fracture classification according to Boyd and Griffin classification, mechanism of trauma, management, and energy of trauma based on the Singh index. The result based on data collected from medical records from January to August 2022, there were 36 intertrochanteric femur fracture patients (8.78%). Intertrochanteric femur fracture patients are mostly found in female patients (25 patients [69.4%]). Based on the age groups, most intertrochanteric femur fracture patients were elderly. Based on the mechanism of trauma, 33 patients had a fracture due to low-energy trauma. According to Boyd and Griffin’s classification, type 2 intertrochanteric femur fracture was more common (14 patients [38.9%]). All patients had PFNA (100%) and most of them had a grade B Singh index (16 patients [44.4%]). Conclusion in this study the incidence of intertrochanteric femur fracture was 8.78%. The intertrochanteric femur fracture was more common in the female patient, aged more than 60 years old, occurs due to low energy trauma, has a type 2 Boyd and Griffin classification, had a grade B Singh index, and was treated using PFNA.